Association of socioeconomic position with insulin resistance among children from Denmark, Estonia, and Portugal: cross sectional study. Issue 7510 (21st July 2005) - Lawlor, Debbie A; Harro, Maarike; Wedderkopp, Niels; Andersen, Lars Bo; Sardinha, Luis B; Riddoch, Chris J; Page, Angie S; Anderssen, Sigmund A; Froberg, Karsten; Stansbie, David; Smith, George Davey
Abstract: Objectives To examine the association between socioeconomic position and insulin resistance in children from three countries in northern Europe (Denmark), eastern Europe (Estonia), and southern Europe (Portugal) that have different physical, economic, and cultural environments. Design Cross sectional study. Participants 3189 randomly selected schoolchildren aged 9 and 15 years from Denmark (n = 933), Estonia (n = 1103), and Portugal (n = 1153). Main outcome measure Insulin resistance (homoeostasis model assessment). Results Family income and parental education were inversely associated with insulin resistance in Danish children but were positively associated with insulin resistance in Estonian and Portuguese children. Among Danish children, insulin resistance was 24% lower (95% confidence interval −38% to −10%) in those whose fathers had the most education compared with those with the least education. The equivalent results were 15% (2% to 28%) higher for Estonia and 19% (2% to 36%) higher for Portugal. These associations remained after adjustment for a range of covariates: −20% (−36% to −5%) for Denmark, 10% (−4% to 24%) for Estonia, and 18% (−1% to 31%) for Portugal. Strong statistical evidence supported differences between the associations in Denmark and those in the other two countries in both unadjusted and adjusted models (all P < 0.03). Conclusions Among Danish children, those with the most educated and highest earning parents had least insulin resistance, whereas the opposite was true for children from Estonia and Portugal.